pcr Standardization to Identify Lawsonia intracellularis in Pigs - Jiménez, Ángela; Luz Stella; Martinez, Marcela; Silva, Yuliana; Florez, Carolina; Mendez, Marcel; Gómez, Anderson (Spei Domus, 2014)
Introduction: the nested Polymerase Chain Reaction (pcr)technique has been standardized for the diagnosis of porcine proliferative enteropathy caused by Lawsonia intracellularis. Methods: such technique was based upon amplifying a region of 270 pb of the 16s arnr gene of the Lawsonia intracellularis. For such purposes, adna sample was taken from the bacteria with a Purelink Genomic kit, Invitrogen ®, from 100 samples of porcine ileum of the metropolitan area of Bucaramanga (Santander). The dna samples were quantified with fluorometry and adjusted to 20 ng/μL concentration. The first amplification of the 319 pb part of the 16s gene was completed with the external initiators: 5’-tat ggc tgt caa aca ctc cg-3’ and 5’-tga agg tat tgg tat tct cc-3’. The result of this first amplification was used as a pattern for the second reaction, where the internal part of 270 pb of the 16s arn gene of L. intracellularis was amplified using the specific internal initiators: 5’- tta cag gtg aag tta ttg gg-3’ and 5’-ctt tct cat gtc cca taa gc-3’. The optimal conditions for the pcr for both internal and external initiators included 2,5 μm de mgcl2; 0,15 μm of each dntp; 1x of reaction buffer; 0,8 μm of each initiator; and 2,5u of Taq polymerase. As a positive control for the taken dna samples and the pcr, the bacterial dna taken from Enterisol ®(Boheringer Ingelheim®) was used. Results: optimal temperatures of annealing for the simple and nested pcr were 50 and 55°C, respectively. The detection limit of the technique was 5 fg. Conclusions: no cross reactions were found with Esquerichia coli, or with Salmonella typhimurium, which are bacteria with similar clinical conditions.